Encyclopaedia Britannica 2001 (Britannica.com.au, 2001)
This database contains the complete text from the Britannica 32-volume print set, the content of the 2000 Britannica Book of the Year, more than 8,500 photos, maps, and illustrations, and direct access to Britannica.com, Britannica`s Web navigation and information service.